Diagnostic Accuracy of Hyomental Distance Ratio (HMDR) for Prediction of Difficult Laryngoscopy in Patients Undergoing Surgery Under General Anesthesia Using Tracheal Intubation - Samina Ashraf, Taoseef Ahmed, Hana Khurshid, Qadeer Ahmed, Kiran Riaz Khan, Tayyeba Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To keep the airway open, a flexible plastic tube (ETT) is inserted into the trachea during tracheal intubation. Even when done correctly, tracheal intubation requires much clinical experience, and catastrophic problems can occur. Mandibular space has been estimated using hyomental distance (HMD), although HMD has only been found to provide a limited amount of diagnostic accuracy on its own. In order to determine how well the Hyomental Distance Ratio (HMDR) predicts difficult laryngoscopy, we conducted this study. Objectives: Using the Cormack and Lehane classification as the gold standard, the objective is to assess the diagnostic validity of the Hyomental Distance Ratio (HMDR) for the prediction of challenging laryngoscopy in patients undergoing surgery under general anaesthesia. Materials & Methods: The department of anesthesiology and the general surgery operating rooms at Sir Ganga Ram Hospital in Lahore conducted this cross-sectional study over the course of six months in 2015–2016. The approach of non-probability purposive sampling was applied. Informed consent was acquired, and patient demographics were recorded. The researcher herself then assessed patients for HDMR. In order to determine if a patient had a difficult or normal laryngoscopy, HDMR was determined. After that, the researcher performed a laryngoscopy on the patients. If the vocal cords were visible, the mouth was opened, and the case was assessed using the Cormack and Lehane classification (CL), with easy or difficult laryngoscopy being designated. SPSS version 20 was used to enter and analyse all of the data. Results: The patients in our study had a mean age of 43.23 11.63 years and a male to female ratio of 1.5:1. In this study, 43.91% of patients had an HDR difficult intubation. HDR's difficult intubation has a sensitivity of 95.05%, a specificity of 96.12%, and a diagnostic accuracy of 95.65% when using CL as the gold standard. Practical Implication: According to this study, this strategy can be applied accurately in other hospitals. Government should establish guidelines for using the most trustworthy techniques as the benchmark in healthcare settings. Conclusion: According to the findings of our study, the HMDR is a viable diagnostic tool for anticipating challenging laryngoscopy in patients having general anaesthesia with tracheal intubation. According to this study, this strategy can be applied accurately in other hospitals. Government should establish guidelines for using the most trustworthy techniques as the benchmark in healthcare settings. Keywords: Laryngoscopy, difficult intubation, Cormack Classification, difficult surgery